2019
DOI: 10.1007/s00018-019-03381-1
|View full text |Cite
|
Sign up to set email alerts
|

Modelling mitochondrial ROS production by the respiratory chain

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(78 citation statements)
references
References 83 publications
3
73
0
2
Order By: Relevance
“…The use of inhibitors of the mitochondrial respiratory chain such as rotenone and antimycin, as well as the substrates for the various complexes such as pyruvate or succinate, have let to the identification of the different complexes involved. To date, complexes I, II, and III have been identified as production sites for superoxide anions [51,52].…”
Section: Mitochondrial Oxidative Stressmentioning
confidence: 99%
“…The use of inhibitors of the mitochondrial respiratory chain such as rotenone and antimycin, as well as the substrates for the various complexes such as pyruvate or succinate, have let to the identification of the different complexes involved. To date, complexes I, II, and III have been identified as production sites for superoxide anions [51,52].…”
Section: Mitochondrial Oxidative Stressmentioning
confidence: 99%
“…ROS production may stem from lysosomes, mitochondria, and imbalance between cellular oxidants and antioxidants; thus, the possible origin of ROS generation in DpdtC-induced growth inhibition needed to be determined. Generally, the main types of ROS from mitochondria are superoxide and peroxide [44], while the hydroxyl radical is mainly due to Fenton reaction occurred in lysosomes or labile iron pool. In our study, DpdtC caused marked decrease of ferritin, accompanied by increasing of NCOA4 and autophagy- related proteins, revealing that the ROS production partly stemmed from the occurrence of ferritinophagy (Figures 2, 3, and S2), in accordance with observation in HepG2 cells reported previously [38].…”
Section: Discussionmentioning
confidence: 99%
“…The general idea of the interplay between depolarization of the mitochondrial membrane and ROS production is that, upon mitochondrial damage or dysfunction, mitochondrial pores open and allowing the in ux of potassium and calcium cations, thereby depolarizing the mitochondrial membrane, which in turn induces ROS production and release. Meanwhile, excessive ROS directly causing the collapse of MMP and depletion of ATP, which later activates a series of signaling pathways that induce apoptosis [29]. Several studies showed prohibitin acts as a coactivator for ARE-dependent gene expression and promotes endogenous antioxidant defense components under oxidative stress [30][31][32].…”
Section: Discussionmentioning
confidence: 99%